Clustering method for bone tissue classification using acoustic emission technique - Mohd Norhafifi, Zainudin (2013)
Bone is one of the important parts of human, as main part of the body it will support the vital internal organs of man and it is also used to move or walk. There are two types of bone structure in the human body that is compact bone and soft bone. Compact bone is located at the top of the bone structure, it is hard and compact. While the soft bone is in bone structure, compact bone below it softer and less dense than compact bone above. This project was undertaken to identify the location of compact bone or soft bone during perforation process underway. With the advent of my study, it can be used as a reference to identify the position of medical officer to penetrate the sides of which are correct or not based the graph. That RMS versus kurtosis, the conclusion if the perforations run and AE signals received from the same or they are in the group of points of reference against kurtosis RMS graph therefore safe position from the position of the spinal cord penetrate.